Application of Simulation Modelling Means in Management Decisions-making within the Security and Defence Sector - Bratko, Artem; Bereziuk, Viktor; Shevchenko, Artem; Kubetsky, Yaroslav; Didyk, Valentyn; Serkhovets, Serhii (Ital Publication, 2021)
Problems and modern tendencies in the field of creating complex models of combat operations are considered. The systematic analysis of existing models of combat operations is carried out and their conformity to modern conditions and development of military art is defined. Features of combat operations models development when using means of simulation modelling are exposed with the use of a method of mathematical simulation. The structure of the complex simulation modelling of actions of forces is formed. The composition of standard models of components of the security and defence sector is determined and the sphere of their application is outlined, which allows controlling the unit in different situations at the stage of choosing decisions at different levels of management. The main directions of the development of modelling complexes and systems are determined. The practical implementation of these approaches, along with the implementation of the principles of cost-effectiveness of models, their coordinated development, system compatibility of models for different purposes and large-scale use of proven commercial decisions will create a cluster of combat operations models, which is a real tool for effective decision-making on troops management and allows laying down technical requirements for the development of a modern complex of simulation modelling.Â Doi: 10.28991/esj-2021-01294 Full Text: PDF